Reunifikasi Sains dan Agama Sebuah Ikhtiar STAIN Purwokerto dalam Mengatai Problem Dikotoministik Ilmu - Slamet Yahya (IAIN Purwokerto, 2014)
Abstract: This research was aimed at explaining the efforts of State College onIslamic Studies (STAIN) of Purwokerto to actualize the reunification of science and religionand the reason why this college implemented such a policy. This is a qualitative researchin which the data were gained through document study, observation, and interview. Thisresearch found that State College on Islamic Studies of Purwokerto actualized thereunification of science and religion through developing its vision and mission into ajargon â€˜STAIN Purwokerto is the Center for Science and Religionâ€™, comprising aspectsof epistemology, axiology, and ontology. Meanwhile the efforts to achieve this ambitionare actualized through balancing the distribution of social and natural science, developinglearning process, developing research programs, developing social work, and developingnetworking with national and international institutions.Keywords: reunification, science, religion. Abstrak: Hasil penelitian ini menunjukkan bahwa dalam upaya paradigmatik STAINdalam mewujudkan reunifikasi sains dan agama adalah dengan mengembangkanVisi dan Misi ke dalam â€œJargon STAIN sebagai Arsy Ilmu dan Agamaâ€, baikdari segi epistemologis, aksiologis, maupun ontologisnya. Upaya akademik STAINdalam mewujudkan reunifikasi sains dan agama pertama; menyeimbangkandistribusi ilmu pengetahuan, khususnya antara ilmu-ilmu sosial-keagamaan danhumaniora dengan ilmu-ilmu eksakta, kedua; pengembangan kegiatan pembelajaran,ketiga; pengembangan penelitian, keempat; pengembangan bidangpengabdian masyarakat, dan kelima; pengembangan networking baik denganinstansi dalam maupun luar negeri.Kata kunci; reunifikasi, sains, agama.